2018
DOI: 10.1155/2018/5081938
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior of Tomato Fiber Suspensions Produced by High Shear and High Pressure Homogenization and Their Application in Tomato Products

Abstract: This study investigated the effects of high shear and high pressure homogenization on the rheological properties (steady shear viscosity, storage and loss modulus, and deformation) and homogeneity in tomato fiber suspensions. The tomato fiber suspensions at different concentrations (0.1%–1%, w/w) were subjected to high shear and high pressure homogenization and the morphology (distribution of fiber particles), rheological properties, and color parameters of the homogenized suspensions were measured. The homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
5
14
0
1
Order By: Relevance
“…The effect of both concentration and temperature treatment on the η ap trend is seen in Figure 6 . Wang et al [ 44 ] indicated that apparent viscosity increased with a rising fiber concentration, which also happened in the results herein shown. Moreover, the apparent viscosity trend increased in the heated samples for all the samples, except for those formulated with FCH and FC, which seemed to follow the same trend in both heated and unheated concentration samples ( Figure 6 a,d).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The effect of both concentration and temperature treatment on the η ap trend is seen in Figure 6 . Wang et al [ 44 ] indicated that apparent viscosity increased with a rising fiber concentration, which also happened in the results herein shown. Moreover, the apparent viscosity trend increased in the heated samples for all the samples, except for those formulated with FCH and FC, which seemed to follow the same trend in both heated and unheated concentration samples ( Figure 6 a,d).…”
Section: Resultssupporting
confidence: 86%
“…Generally speaking, in the samples with lower fiber content, solid content was precipitated, but the uniformity of suspensions markedly increased when concentration rose. This could be due to the fact that samples are mixtures of whole cells and dispersed cell wall materials, and it has been reported that these materials usually form non homogeneous suspensions, unlike smashed cellular material that forms homogeneous fibrous networks [ 44 ]. However, homogeneity increased while fiber concentration increased due to the mixture’s saturation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, dietary fibre intake was self-reported, most of the time using FFQ which, even if validated, cannot prevent recall bias or social desirability bias, thus both resulting in mis-reporting. Secondly, information on cooking methods were not assessed and reported in the original studies, and recent evidence showed a modification in the fibre structure and biological effect based on the processing method used [ 68 , 69 ]. Thirdly, in the main analysis, the funnel plot confirmed by the Egger’s test showed a potential publication bias.…”
Section: Discussionmentioning
confidence: 99%
“…Because of recall and social desirability bias, misclassification or under/over-reporting of fibre intake might result in a modified grade of association. Furthermore, no information on processing methods are reported in the original studies, and according to recent evidence, the processing method is associated with alteration of fibre microstructure that in turn is associated with changes in biological effects [46,47]. All the above-mentioned limits are mainly due the primary study design, and even if we conducted a risk of bias evaluation and several adaptations (for instance, groups analysis and adjusted risk), it is not possible to estimate the impact of this potential misclassification.…”
Section: Discussionmentioning
confidence: 99%